On Indian ground : the Southwest - Tippeconnic, John; Fox, Mary Jo Tippeconnic (On Indian ground., 2021)
"On Indian Ground: The Southwest is one of ten regionally focused texts that explores American Indian/Alaska Native/Native Hawaiian education in depth. The text is designed to be used by educators of native youth and emphasizes best practices found throughout the state. Previous texts on American Indian education make wideranging general assumptions that all American Indians are alike. This series promotes specific interventions and relies on native ways of knowing to highlight place-based educational practices. On Indian Ground: The Southwest looks at the history of Indian education within the southwestern states. The authors also analyze education policy and tribal education departments to highlight early childhood education, gifted and talented educational practice, parental involvement, language revitalization, counseling, and research. These chapters expose cross-cutting themes of sustainability, historical bias, economic development, health and wellness and cultural competence. The intended audience for this publication is primarily those educators who have American Indian/Alaska Native/Native Hawaiian students in their educational institutions. The articles range from early childhood and head start practices to higher education, including urban, rural and reservation schooling practices. A secondary audience: American Indian education researcher"--